The Impact of Liquidity, Profitability, and Leverage on Firm Value with Dividend Policy as a Moderating Variable: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange (2020–2024) - Yang, Vandwuis; Gultom, Juan barus (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2025)
The performance of Indonesia’s manufacturing sector in the first half of 2024 experienced a slowdown, as reflected by a three-consecutive-month decline in the Purchasing Managers’ Index (PMI), reaching 50.7 in June 2024. This downturn affected the industrial and consumer goods sector indices and weakened the financial performance of several major listed companies, such as PT Astra International Tbk (ASII). The decline in demand, higher production costs, and global economic uncertainty have contributed to reduced investor confidence, which in turn influences fluctuations in firm value across the sector. This situation has encouraged companies to carefully manage financial indicators to maintain their competitiveness and attractiveness in the capital market. This study aims to examine the effect of liquidity, profitability, and leverage on firm value, with dividend policy as a moderating variable, focusing on manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Purposive sampling was applied, resulting in 22 companies (110 observations), and the data were analyzed using SPSS version 25 with normality, multicollinearity, and heteroscedasticity tests, Moderated Regression Analysis (MRA), coefficient of determination (R²), and t-tests. Furthermore, this research period includes the post-pandemic recovery phase, where many companies are adjusting their financial strategies to stabilize operations. The findings indicate that liquidity, profitability, and leverage significantly affect firm value. Companies with strong liquidity and healthy profitability levels tend to gain more investor trust, while excessive leverage may increase financial risk. Dividend policy moderates the effect of liquidity on firm value but does not moderate the effects of profitability and leverage on firm value. This suggests that dividend decisions can strengthen investor perceptions when liquidity is high, yet may not be influential when profitability or leverage factors dominate managerial considerations.